The use of online learning videos in BIPA program for Arabic speakers - Rinaldi Supriadi; Mia Nurmala (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
This research departs from developing BIPA teaching materials for Arabic speakers. Teaching materials are made in form of interactive learning videos presenting cultural diversity and Indonesian local wisdom. Furthermore, these BIPA learning videos are shared on social media. Therefore, learners of Arabic BIPA from various countries in the Middle East can access this material teaching. A qualitative descriptive method was used in this study. The data were obtained from observation, interviews, and documentation. The study used purposive sampling. The study results stated that those learning videos were based on the BIPA learning syllabus determined by the Ministry of Education and Culture. Furthermore, these learning videos are presented in a cultural package with Arabic as the language of instruction. By sharing the videos on social media, this video can help learners without the limitations of space and time